Adrenal Cortical Adenoma Resulting from Congenital Adrenal Hyperplasia Managed with Unilateral Laparoscopic Adrenalectomy: A Case Report - Didik Supriyadi Kusumo B; M. Robikhul Ikhsan (‎ InaJEMD - Indonesian Journal of Endocrinology Metabolic and Diabetes, 2024)
Congenital adrenal hyperplasia (CAH) is an autosomal recessive disorder resulting from mutations in genes encoding enzymes involved in cortisol biosynthesis. Over 90-95% of cases are caused by 21-hydroxylase deficiency, with an incidence of 1:10,000-1:20,000 among Caucasians. This condition leads to cortisol deficiency, causing a loss of negative feedback in the pituitary gland and subsequently increased secretion of adrenocorticotropic hormone (ACTH), which in turn stimulates the production of adrenal androgens and adrenal hyperplasia. We report a 31-year-old female with classic CAH of the simple virilizing subtype and a history of genital reconstruction due to external genital ambiguity. She received glucocorticoid therapy and spironolactone to block androgen receptors. As a result, hirsutism decreased, and MRI evaluation of the adrenal glands revealed a reduction in size compared to pre-treatment (bilateral adrenal gland enlargement). No disturbances due to mineralocorticoid receptor blockade from spironolactone administration were found. In the fourth-year MRI evaluation, the left adrenal gland was larger than normal, while the right was within normal limits. A functional left adrenal gland tumor T1N0M0 was concluded, and a left laparoscopic adrenalectomy was decided upon. The patient consented to the procedure one year later. Laparoscopic adrenalectomy of sinistra was successfully performed with histopathologic examination revealed adrenal cortical adenoma. Monitoring and evaluation of clinic visits, we concluded that unilateral adrenalectomy cannot replace routine medication, but can reduce the dose requirement. Currently, the patient is still under regular control and supervision to evaluate the long-term results of the procedure whether there is a risk of adrenal crisis, whether it can overcome the effects of hyperandrogenism, and whether there is an adrenal rest tumor.